2021
DOI: 10.3390/ijerph182111319
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the COVID-19 Transmission Misinformation Scale and Conditional Indirect Negative Effects on Wearing a Mask in Public

Abstract: The SARS-CoV-2 (COVID-19) pandemic devastated the world economy. Global infections and deaths altered the behaviors of generations. The Internet acted as an incredible vehicle for communication but was also a source of unfounded rumors. Unfortunately, this freedom of information sharing and fear of COVID-19 fostered unfounded claims about transmission (e.g., 5G networks spread the disease). With negligible enforcement to stop the spread of rumors and government officials spouting unfounded claims, falsities be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 136 publications
(186 reference statements)
0
16
1
Order By: Relevance
“…The COVID-19 Transmission Misinformation Scale (CTMS) was established by Bok et al (2021) . There are 12 items on the scale, with five levels: 1 = “strongly disagree,” 2 = “highly disagree,”3 = “hesitate,” 4 = “agree,” 5 = “firmly agree.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 Transmission Misinformation Scale (CTMS) was established by Bok et al (2021) . There are 12 items on the scale, with five levels: 1 = “strongly disagree,” 2 = “highly disagree,”3 = “hesitate,” 4 = “agree,” 5 = “firmly agree.”…”
Section: Methodsmentioning
confidence: 99%
“…To avoid misleading and ambiguous language, and to prevent any unclear content from becoming disinformation, it is vital to stress each element in a piece of health information (Chen et al, 2021). Chen et al (2021) Bok et al (2021) contains an item on 5G networks; however, 5G networks are uncommon in Vietnam, and the research team has not adjusted the content of the item to suit the development in Vietnam. Future studies should consider adjusting the content of items to suit the context at the time of research.…”
Section: Implicationmentioning
confidence: 99%
“…It is also worth mentioning several studies examining in detail the rumors, myths and hypotheses associated with COVID-19 and their direct connection to the perceptions of the pandemic. Thus, aspects considered range from climate and natural factors (4,5) to the dis-and misinformation disseminated in social and mass media sources (6). Therefore, the theoretical basis of our study was expanded and included several aspects of the intended analysis of COVID-19 media discourse in the Russian Federation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some have shown that the need for information in times of crises combined with the public nature of social media are important reasons for the spread of inaccurate information [ 58 ]. Most fabrication revolved around COVID-19’s statistics, origins, transmission, prevention and treatment [ 58 , 59 ]. False narratives can affect people’s health and safety, as is the case of mistrusting mask regulations or the false rumors surrounding hydroxychloroquine’s therapeutic efficacy [ 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most fabrication revolved around COVID-19’s statistics, origins, transmission, prevention and treatment [ 58 , 59 ]. False narratives can affect people’s health and safety, as is the case of mistrusting mask regulations or the false rumors surrounding hydroxychloroquine’s therapeutic efficacy [ 59 , 60 ]. Furthermore, this atmosphere of mistrust can lead to negative psycho-social outcomes with economic and ethical healthcare considerations [ 58 ].…”
Section: Introductionmentioning
confidence: 99%